Sharing and Jumping Based Didactical Design In Collaborative Learning on the topic of Covalent Bonding - Ermila Gustina; Sumar Hendayana; Asep Supriatna (Universitas Negeri Padang, 2018)
The effectiveness of sharing and jumping based didactical design of covalent bonding has been studied at chemistry senior high school. Learning based sharing task is a learning that deals to cover content of text book. Sharing task facilitate jumping process for the low achiever students. The challenging problems are given in jumping tasks activity to challenge the high achiever students. The purpose of this study was to obtain the didactical design of covalent bondings and their implementation.The research method applied is Didactical Design Research (DDR) with following stages: analysis of didactic situation before learning, metapedadidactical analysis, and retrospective analysis. Implementation of lesson design on the topic of covalent bonding were recorded and analyzed, from the analysis result obtained the collaboration between students and between students and teachers.